Changes in Higher-Order Chromosomal Structure of Klebsiella pneumoniae Under Simulated Microgravity - Wang, Yahao; Shen, Wenlong; Yin, Man; Huang, Wenhua; Ye, Bingyu; Li, Ping; Shi, Shu; Bai, Ge; Guo, Xinjie; Jin, Yifei; Lin, Kailin; Zhang, Yan; et al. (Frontiers in Microbiology, 2022)
Our previous work have shown that certain subpopulations of Klebsiella pneumoniae exhibit significant phenotypic changes under simulated microgravity (SMG), including enhanced biofilm formation and cellulose synthesis, which may be evoked by changes in gene expression patterns. It is well known that prokaryotic cells genomic DNA can be hierarchically organized into different higher-order three-dimensional structures, which can highly influence gene expression. It is remain elusive whether phenotypic changes induced by SMG in the subpopulations of K. pneumoniae are driven by genome higher-order structural changes. Here, we investigated the above-mentioned issue using the wild-type (WT) K. pneumoniae (WT was used as a control strain and continuously cultivated for two weeks under standard culture conditions of normal gravity.) and two previous identified subpopulations (M1 and M2) obtained after two weeks of continuous incubation in a SMG device. By the combination of genome-wide chromosome conformation capture (Hi-C), RNA-seq and whole-genome methylation (WGS) analyses, we found that the along with the global chromosome interactions change, the compacting extent of M1, M2 subpopulations were much looser under SMG and even with an increase in active, open chromosome regions. In addition, transcriptome data showed that most differentially expressed genes (DEGs) were upregulated, whereas a few DEGs were downregulated in M1 and M2. The functions of both types DEGs were mainly associated with membrane fractions. Additionally, WGS analysis revealed that methylation levels were lower in M1 and M2. Using combined analysis of multi-omics data, we discovered that most upregulated DEGs were significantly enriched in the boundary regions of the variable chromosomal interaction domains (CIDs), in which genes regulating biofilm formation were mainly located. These results suggest that K. pneumoniae may regulate gene expression patterns through DNA methylation and changes in genome structure, thus resulting in new phenotypes in response to altered gravity.